The Development and Implementation of a Participatory and Solution-Focused Framework for Clinical Research: A case example - Walsh, K.; Ford, K.; Morley, C.; McLeod, E.; McKenzie, D.; Stafford, Leanne; Gordon-Croal, S.; Peterson, G. (Elsevier BV, 2017)
© 2016 Australian College of Nursing Ltd.Implementing evidence-based practice change in healthcare can be difficult. However, a number of factors can enable the implementation of evidence-based care. Some of these factors are: commitment to a shared purpose, openness and sharing of ideas, and relationships building. This paper focuses on the translational research methodological processes that were developed and used to implement practice change, and draws on a case example of a multidisciplinary project in a Tasmanian hospital. The project aimed to improve patient outcomes by reducing the incidence of omitted or delayed administration of prescribed medications. The participatory, collaborative research framework developed drew upon principles from practice development, knowledge translation and facilitation.Central to the work was a person-centred and solution-focused, strengths-based approach. The approach incorporated a framework made up of six key elements: engagement, evidence, context, facilitation, implementation and evaluation. Staff were acknowledged as context experts and the work was informed by the view that sustainable, effective solutions should be developed in collaboration with staff. Staff, including technicians, volunteers, medical, nursing and pharmacy staff, were co-researchers in identifying, implementing and evaluating context-specific solutions. Their participation and inclusion led to the identification of a number of innovative solutions to the complex, shared practice puzzle of omitted medications. Person-centred ways of working that were respectful and collaborative meant there was effective engagement and changes to practice. Staff evaluations of the overall study approach were very positive. Whilst the study was led by a team of pharmacists and nurses, the framework used is applicable to nursing-led initiatives and is transferable to other clinical contexts.